2020
DOI: 10.2147/idr.s277295
|View full text |Cite
|
Sign up to set email alerts
|

<p>In-vitro Antimicrobial Activity of Essential Oils and Spices Powder of some Medicinal Plants Against <em>Bacillus</em> Species Isolated from Raw and Processed Meat</p>

Abstract: Background and Aim: Bacillus species are widely distributed microorganisms in nature that are responsible for outbreaks of food poisoning and a common cause of food spoilage. This study aimed to isolate and identify foodborne Bacillus species from meat and to determine the antimicrobial activities of commercial essential oils and spices powder extracted from certain medicinal plants. Methods: Sixty meat samples were collected in Assiut city and subdivided into raw meat and processed meat. Bacillus spp were iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 57 publications
0
9
0
1
Order By: Relevance
“…In light of this result, the decrease in the microbial count could be attributed to the antibacterial activity of these spices powder. Recently, it has been reported that both essential oils and spices powder have antibacterial activity against Bacillus species [41].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In light of this result, the decrease in the microbial count could be attributed to the antibacterial activity of these spices powder. Recently, it has been reported that both essential oils and spices powder have antibacterial activity against Bacillus species [41].…”
Section: Discussionmentioning
confidence: 99%
“…The 16S rRNA was amplified using the universal primers 27F and 1492R, as previously described by Lane [39]. The PCR conditions were as follows: 94 • C for 5 min followed by 30 cycles of 40 s at 94 • C, 30 s at 52 • C, and 1 min at 72 • C. A final 7 min extension step was done at 72 • C [40,41].…”
Section: Isolation and Identification Of Some Bacterial Species In The Meat Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were in accordance with those obtained after the pre-treatment of the meat with the commercial essential oil which induced a significant decrease of Bacillus spp. This latter was found to be very sensitive to the EO and the NS powder [ 55 ] ( Table 2 ).…”
Section: Pharmacological Properties Of Nigella Sativamentioning
confidence: 99%
“…Interestingly, SR‐BI is involved in various types of infections, it is regarded as receptor entry for mycobacterium and hepatitis C virus (HCV) 9 . However, deficiency of SR‐BI did not affect the disease severity and high cholesterol enhances bacterial and viral burdens in the lung independent of SR‐BI expression 9–11 …”
Section: Introductionmentioning
confidence: 99%